The Effect of Social Media Use Intensity on Body Image Dissatisfaction in Early Adult Women - Fadhilah Aprilia Lukman; Ismarli Muis; Andi Nasrawati Hamid (Universitas Muhammadiyah Surakarta, 2023)
Social media plays a significant role in the development of dissatisfaction with one's body image, primarily attributed to the proliferation of digital communication tools. Excessive engagement with social media platforms could contribute to a negative perception of one's body image and subtly impact an individual's perception of beauty ideals. This can be observed through the sharing of photos that strictly adhere to societal standards of flawlessness and perfection. This study examined the intensity of social media use on body image dissatisfaction in early adult women. This research focused on early adult women aged 18-25 in Indonesia. Data was collected from 304 women using the Social Networking Time Use Scale (SONTUS) and the Body Image Dissatisfaction Scale (BID Scale). Five aspects of social media intensity were analyzed to determine their impact on five dimensions of body image dissatisfaction. The result of regression analysis showed that the social media use intensity positively affects body image dissatisfaction. Active users of social media would develop body image dissatisfaction. This study suggests that the more frequently young women use social media, the more dissatisfied they become with their body image. Furthermore, social media use intensity influenced all dimensions of body image dissatisfaction, including appearance evaluation, appearance orientation, body area satisfaction, overweight preoccupation, and self-classified weight.